Self-propelled carbon nanotube based microrockets for rapid capture and isolation of circulating tumor cells1. Issue 19 (21st May 2015) - Banerjee, Shashwat S.; Jalota-Badhwar, Archana; Zope, Khushbu R.; Todkar, Kiran J.; Mascarenhas, Russel R.; Chate, Govind P.; Khutale, Ganesh V.; Bharde, Atul; Calderon, Marcelo; Khandare, Jayant J.
<x xml:space="preserve">Abstract</x> Here, we report a non-invasive strategy for isolating cancer cells by autonomously propelled carbon nanotube (CNT) microrockets.